Postoperative fluid overload is a risk factor for adverse surgical outcome in patients undergoing esophagectomy for esophageal cancer: a retrospective study in 335 patients. Issue 1 (December 2017) - Glatz, Torben; Kulemann, Birte; Marjanovic, Goran; Bregenzer, Svenja; Makowiec, Frank; Hoeppner, Jens
Abstract Background Restrictive intraoperative fluid management is increasingly recommended for patients undergoing esophagectomy. Controversy still exists about the impact of postoperative fluid management on perioperative outcome. Methods We retrospectively examined 335 patients who had undergone esophagectomy for esophageal cancer at the University Hospital Freiburg between 1996 and 2014 to investigate the relation between intra- and postoperative fluid management and postoperative morbidity after esophagectomy. Results Perioperative morbidity was 75%, the in-hospital mortality 8%. A fluid balance above average on the operation day was strongly associated with a higher rate of postoperative mortality (21% vs 3%, p  < 0.001) and morbidity (83% vs 66%, p  = 0.001). Univariate analysis for risk factors for adverse surgical outcome (Clavien ≥ III) identified ASA-score (p  = 0.002), smoking (p  = 0.036), reconstruction by colonic interposition (p  = 0.036), cervical anastomosis (p  = 0.017), blood transfusion (p  = 0.038) and total fluid balance on the operation day and on POD 4 (p  = 0.001) as risk factors. Multivariate analysis confirmed only ASA-score (p  = 0.001) and total fluid balance (p  = 0.001) as independent predictors of adverse surgical outcome. Conclusion Intra- and postoperative fluid overload is strongly associated with increased postoperative morbidity. Our results suggest restrictive intra- and especially postoperative fluid management to optimize the outcome after esophagectomy.